THE IMPACT OF INDIVIDUAL FACTORS, ORGANIZATIONAL CULTURE AND JOB OPPORTUNITIES ON TURNOVER INTENTION AT BANK SULUTGO AMURANG - Rawis, Chrestini; Lapian, Stanss L. H. V. J.; Mangantar, Maryam (Universitas Sam Ratulangi, 2021)
Turnover Intention of employees in organization is a one of the biggest issues that can happen in a company especially in bank and financial industry. The desire to leave from employees can affect to their performance to the company, and more impact that can happen when employees decided to leave the job; for example loss fund and time. There are many factors that make employees think about leaving the company. This study take three factors such as, Individual Factors as internal factor within employees, Organizational Culture as factor that can handled by the company and Job Opportunities as external factor that come from outside company. This research objective is to reveal the effect of Individual Factors, Organizational Culture and Job Opportunities on Turnover Intention. This research was classified as quantitative research that use questionnaire and distributed to 51 respondents by the link at Bank SulutGO Amurang. This research used Sensus (saturated) techniques sampling. By using Multiple Linear Regression method, this study found that Individual Factors has no significant effect on Turnover Intention partially, Organizational Culture has a negative significant effect on Turnover Intention partially, and Job Opportunities has a positive significant effect on Turnover Intention partially, but simultaneously have an effect on Turnover Intention. It can be seen where the sig. level of Individual Factors is 0.121 greater than 0.05 as the significance level of testing hypothesis.Â Keyword: individual factors, organizational culture, job opportunities, turnover intention